Developing the systems thinking skills of pre-service science teachers through an outdoor ESD course - Karaarslan Semiz, Güliz; Teksöz, Gaye (Journal of Adventure Education and Outdoor Learning, 2020)
The purpose of this study is to explore the development of pre-service science teachers’ systems thinking skills through an outdoor education for sustainable development (ESD) course. The study was composed of four stages, which are defining systems thinking skills, designing an outdoor ESD course, developing measurement tools, and implementation. Twelve systems thinking skills were determined within the ESD and science education context. Qualitative data were collected through interviews and systems thinking skill levels were evaluated based on the rubric developed by the authors. Participants showed a slow improvement in four systems thinking skills which are related to considering the relationship between past, present and future, developing empathy with non-human beings, developing sense of place and adapting systems thinking perspective to personal life. There is a need to test the hierarchical level among the twelve systems thinking skills in future studies and to study each skill in different contexts.
Keywords: Systems thinking skills; education for sustainable development; outdoor education; pre-service science teachers